2019
DOI: 10.1109/access.2019.2907050
|View full text |Cite
|
Sign up to set email alerts
|

Rolling Bearing Incipient Degradation Monitoring and Performance Assessment Based on Signal Component Tracking

Abstract: To ensure a long-time stable operation of the rolling bearing, it is important to accurately assess their working performance, especially the incipient degradation based on the massive service process data. As a new and effective tool, deep learning model is applied widely in the field of fault diagnosis but limited to rare labeled data. In this paper, a bearing performance assessment method based on signal component tracking is proposed to realize the bearing degradation detection. More general features are o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…However, the process might not work well for transient or stationary signals whose frequency components vary in time, usually the case in the real world. For non-stationary signals, it is common to transform the raw signals into the time-frequency domain using Short Time Fourier Transform (STFT) [92]- [94], Wavelet Transform (WT) [95]- [98] or Empirical Mode Decomposition (EMD) [99], [100]. STFT adopts a window function of fixed length, thus suffering from the time-frequency resolution trade-off problem.…”
Section: ) Vibration Datamentioning
confidence: 99%
See 1 more Smart Citation
“…However, the process might not work well for transient or stationary signals whose frequency components vary in time, usually the case in the real world. For non-stationary signals, it is common to transform the raw signals into the time-frequency domain using Short Time Fourier Transform (STFT) [92]- [94], Wavelet Transform (WT) [95]- [98] or Empirical Mode Decomposition (EMD) [99], [100]. STFT adopts a window function of fixed length, thus suffering from the time-frequency resolution trade-off problem.…”
Section: ) Vibration Datamentioning
confidence: 99%
“…Note that signals in the time-frequency domain naturally have a two-dimensional form, making them suitable for the input of a traditional CNN. After a proper normalization step, those time-frequency domain signals were treated as images and various CNN-based variants were built by [92], [94]- [98], [101], [106], [107].…”
Section: ) Vibration Datamentioning
confidence: 99%
“…This interference often leads to a decrease in the diagnostic accuracy of intelligent diagnostic models. Dong et al [64] proposed a method for bearing performance evaluation based on signal component tracking to detect bearing degradation. This approach incorporates abnormal information in degradation monitoring to facilitate initial bearing fault diagnosis, demonstrating high efficiency in early fault detection and diagnosis.…”
Section: Analysis Of Co-cited Literaturementioning
confidence: 99%
“…The collected vibration signals of the bearing are easily disturbed by heavy background noise, which causes the fault characteristic frequency to be buried, and the fault cannot be diagnosed effectively. To solve the difficulty in feature information extraction of rolling bearings with early weak faults, various signal processing methods have been proposed and applied successively, such as the short-time Fourier transform [5], Wigner-Ville distribution [6], and wavelet transform (WT) [7] Huang et al Although the above time-frequency analysis methods are shown to have certain improvements over the traditional signal analysis methods, they lack decomposition adaptivity. In recent years, some scholars have proposed adaptive signal decomposition methods for the fault diagnosis of rolling bearings, such as empirical mode decomposition (EMD) [8] and its variants , local mean decomposition [9], local characteristicscale decomposition [10], singular value decomposition [11], and empirical wavelet transform [12] etc.…”
Section: Introductionmentioning
confidence: 99%